The efficacy of acute nutritional interventions on soccer skill performance - Russell, M.; Kingsley, M. (Sports Medicine, 2014)
Background: The use of nutritional ergogenic aids in team sports such as soccer is now commonplace. Aligned with the primary aim of soccer, which is to score more goals than the opposition within the allotted time, the quality of performance of technical actions (i.e., skills) executed during soccer-specific exercise is likely to determine success. However, when seeking to maintain soccer skill performance, information about the efficacy of nutritional interventions is lacking and factors which might modulate the efficacy of such strategies are unclear. Objective: This review aimed (i) to systematically evaluate the current research that examines the efficacy of nutritional interventions on soccer skills, and (ii) to provide a qualitative commentary on factors that have the potential to modulate the efficacy of such strategies. Data Sources: Relevant databases (PubMed and SPORTDiscus) were searched up to and including 1 July, 2013 for studies that investigated the efficacy of acute nutritional interventions on soccer skill performances. Study Selection: Overall, 279 records were retrieved. Articles were sequentially excluded from the review based on specific criteria, being: (A) articles that did not report outcomes directly relating to skilled performances in soccer, (B) articles that examined the influence of interventions that were not nutritional in origin and/or were nutritional in origin but provided >3 hours before skill testing commenced, (C) articles that were review papers, and (D) post-acceptance withdrawal of articles methods from database. Study Appraisal and Synthesis Methods: Articles were independently assessed for the quality of the methods employed based upon the Physiotherapy Evidence Database (PEDro) scale. Records achieving a minimum PEDro score of 5 out of 10 were included in this review. Qualitative appraisal of 13 articles was performed after the application of exclusion criteria and quality assurance processes. The majority (n = 8) of articles examined the influence of carbohydrates on technical performance whereas fewer studies investigated the influence of caffeine ingestion (n = 2) and fluid provision (n = 3). Results: Findings were reported for a total of 171 participants and all but one of the included articles used cross-over study designs. Most participants (94 %) were male, highly trained (reported maximal aerobic capacity range 50-59 ml/kg/min) and exercised in temperate environments (reported temperature range 13-25 °C). Six of the eight studies reported that carbohydrates, consumed in the form of a 6-8 % solution of glucose, sucrose or maltodextrin at rates of 30-60 g/h, enhanced at least one aspect of skilled performance over the duration of exercise (75-90 min). Although some evidence exists to support the consumption of caffeine (6 mg/kg body mass [BM]) and prescribed fluid to preserve skills performed during soccer-specific exercise, findings from the small number of included studies were inconsistent. Limitations: The outcome measures and methods used to quantify skilled performance were not consistent across studies; consequently, it was not possible to perform meta-analyses to produce pooled effect sizes in this review. Conclusions: The findings from this systematic review suggest that nutritional interventions, which provide carbohydrate, caffeine and fluid, have potential to preserve skills performed under conditions that induce soccer-specific fatigue. The weight of current evidence supports the consumption of carbohydrate, but is less conclusive with respect to caffeine and fluid provision. It is likely that the efficacy of a nutritional intervention will be modulated by factors including the dose consumed, the mode of administration, individual responsiveness to the intervention and interactions with other physiological changes occurring during soccer-specific exercise. Consequently, these factors should be considered when using carbohydrates, caffeine and fluid provision to maintain skilled performances in soccer. Future research should seek to optimise the nutritional strategies employed to maintain technical performance throughout match-play.